Empowerment, Task Commitment, and Performance Pay - Beckmann, Michael; Kräkel, Matthias (Journal of Labor Economics, 2022)
Although from the viewpoint of social psychology task commitment is a driving force for intrinsic motivation in the workplace, this topic has been widely ignored in labor and personnel economics so far. Our paper reduces this gap in the literature by offering a theoretical analysis of worker empowerment and task commitment. This approach also helps to explain the observed variety of compensation schemes across workers and firms. By using a large-scale linked employer-employee panel data set, we present empirical evidence that is consistent with the predicted patterns of our theoretical model.